Analysis of goals in under-17 futsal games during the São Paulo championship 2012 - Campos, Jussie Melo (2013)
Introduction: Currently, futsal is a unpredictablegameand there are several possibilities of goals. Objective:Theobjective of this study was to analyze how the goals occurred in the games of the São Paulochampionship 2012. Materials and methods: Were analyzed technical tactical actions. The sample consisted of shooting 6 of 10 first roundsmatches of the 2012 state team. Data were recorded in Excel 2007. The method adopted was quantitative. Resultsand Discussion: In the resultsthe technical-tactical actions that stood out over the others were the moves combined and individual plays with 40%and 23% respectively. The moves set pieces resulted in 20%, representing a substantial number of total goals in the games studied. Conclusion: It can be concluded that there is an advantage in goals in the context of technical-tactical Combined Played and played-pieces were also significant in the research.